อิสรภาพและการเล่นในคัมภีร์จวงจื่อ - ธนวัฒน์ วุฒิศิริศาสตร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This thesis aims to study the notion of freedom and play in the Zhuangzi and proposes that the analytical framework of play in 6 aspects of meaning of play, namely, play as action, play as interaction, play as activity, play as disposition, play as experience, and play as context, would help highlight the notion of freedom in the Zhuangzi clearly—not only freedom in thoughts and feelings achieved through spiritual transformation, but also especially freedom to navigate one’s life to achieve certain goals. This thesis directs the connection between play and the state of being free of a player or a so-called "true person," in which the training of play is ultimately an empowerment of normal and disadvantaged persons that they can as well "apply" and transfer mastery to play, having emptiness as an important characteristic of play, to a bigger playground, from private ground to public ground. A true person who can truly play would succeed in every ground they involve and be able to nourish his life and those he plays with. Last but not least, play is Zhuangzi’s proposal that invites humans to unbind themselves, which is primarily self-bound by knowledge and individual understandings, thus opening a wide range of possibilities in life among diversity, with playfulness and pleasure, and embracing the state of being free.